2002
DOI: 10.1023/a:1014832416073
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This paper continues a series of reports considering nitric oxide (NO) and its cyclic conversions in mammals. Numerous facts are summarized with the goal of developing a general concept that would allow the statement of the multiple effects of NO on various systems of living organisms in the form of a short and comprehensive law. The current state of biological aspects of NO research is analyzed in term of elucidation of possible role of these studies in the system of biological sciences. The general concept i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 25 publications
0
31
0
Order By: Relevance
“…Several biological phenomena such as hypoxia is beset with the conditions where NOS is compromised, where the utilization of nitrates for the production of NO is encountered. 1) Nitrite reductase (NR) originally described in plants is discernible in microorganisms as well as mammalian cells. Panesar and Chan reported the NR activity in Mouse Leydig Tumor Cells and was attributed to mitochondrial respiratory chain complex III.…”
mentioning
confidence: 99%
“…Several biological phenomena such as hypoxia is beset with the conditions where NOS is compromised, where the utilization of nitrates for the production of NO is encountered. 1) Nitrite reductase (NR) originally described in plants is discernible in microorganisms as well as mammalian cells. Panesar and Chan reported the NR activity in Mouse Leydig Tumor Cells and was attributed to mitochondrial respiratory chain complex III.…”
mentioning
confidence: 99%
“…Anomalies in the subionospheric propagation of very low frequency (VLF) transmitter signals associated with earthquakes have been reported by Morgounov et al (1994) and Hayakawa et al (1996a). Reutov and Marenko (1995) reported optical emissions (night airglow) approximately two days before the earthquake and also suggested that their optical emissions are connected with increasing plasma density anomalies at the F 2 layer or processes at the E-layer. A brief account of effects of seismic activities on the E-and F-regions of the ionosphere can be found in the paper by Pulinets et al (1994).…”
Section: Introductionmentioning
confidence: 87%
“…High-capacity NO production in eukaryotic systems has two dominant but not unique routes: 1) the primary production via enzymatic oxygenation of the guanidine group of L-arginine to form NO and L-citrulline by a specific enzyme, NO synthase (NOS) [17]; and 2) the secondary production by enzymatic reduction of nitrite [18,19] via nitrite reductase activity (NRA) of xanthine oxidase [20,21], mitochondrial cytochrome complexes [22,23], deoxyhemoglobin [24][25][26], and some NOS isozymes under anoxic conditions [27]. It is generally assumed that the primary NO synthesis from L-arginine oxidation by NOS and following retrograde diffusion of the gaseous messenger is responsible for focal "neurotransmitter-like" actions of NO [28], as well as for pathogen-induced escalation of cytotoxic defense [29].…”
Section: No Productionmentioning
confidence: 99%
“…In contrast, the secondary NO formation route from nitrite anion is believed to be a basis of tonic circulation and retrograde "hormone-like" action of NO in organisms [30]. The latter also appears to be a fundamental mechanism for recycling of NO in cell, tissue, and whole organism [18,19]. Since NO synthesis from L-arginine oxidation and nitrite reduction varies in time and space, the contribution of both pathways should be considered in each particular bioanalytical scenario.…”
Section: No Productionmentioning
confidence: 99%
See 1 more Smart Citation